New species and records of the symbiotic shrimp genus Leptalpheus Williams, 1965, with notes on Fenneralpheus Felder & Manning, 1986, and preliminary molecular analysis of phylogenetic relationships (Crustacea: Decapoda: Alpheidae) - Scioli, Justin A.; Robles, Rafael; Felder, Darryl L. (Zootaxa, 2024)
The shrimp genera Leptalpheus Williams, 1965 and Fenneralpheus Felder & Manning, 1986 are composed entirely of symbiotic species that co-inhabit burrows of infaunal macrocrustaceans. We report extensive collections of these genera from western Atlantic, eastern Pacific and Indo-West Pacific regions. Integrative taxonomy methods, including morphological comparisons and analysis of three mitochondrial genetic markers, are used to test species hypotheses and evolutionary relationships among members of these genera. Our molecular analysis failed to recover Leptalpheus or Fenneralpheus as monophyletic groups. Our results strongly supported the monophyly of three clades composed of species of Leptalpheus, loosely corresponding to previously proposed species groups. Three new species closely related to Leptalpheus forceps Williams, 1965, L. marginalis Anker, 2011, and L. mexicanus Ríos & Carvacho, 1983 are described. Leptalpheus ankeri n. sp., from the Caribbean Sea, Atlantic coast of Florida, and Gulf of Mexico, is a polymorphic species that exhibits two major cheliped morphotypes. Leptalpheus sibo n. sp., from the Pacific coast of Nicaragua, is morphologically very similar to L. ankeri n. sp., likely its transisthmian sister species, and shares its cheliped polymorphism. A reassessment of L. forceps concluded that records of this species from the Caribbean Sea and Brazil are not conspecific with L. forceps sensu stricto from the Atlantic coast of the USA and the Gulf of Mexico, and they are herein described as Leptalpheus degravei n. sp. Based on both molecular and morphological evidence, we found Leptalpheus bicristatus Anker, 2011 to be a junior synonym of L. mexicanus and Leptalpheus canterakintzi Anker & Lazarus, 2015 to be a junior synonym of Leptalpheus azuero Anker, 2011. First reports of Leptalpheus axianassae Dworschak & Coelho, 1999 in Texas and Mexico, Leptalpheus denticulatus Anker & Marin, 2009 in the Mariana Islands, Leptalpheus felderi Anker, Vera Caripe & Lira, 2006 and Leptalpheus lirai Vera Caripe, Pereda & Anker, 2021 in the USA, and Leptalpheus pereirai Anker & Vera Caripe, 2016 in Cuba are included.